Risk of Prostate Cancer in Chronic Kidney Disease Patient: A Meta-Analysis using Observational Studies - Othman Khalid AlOmeir (Wolters Kluwer Medknow Publications, 2023)
Background: Both clinical and experimental findings demonstrated a rise in prostate cancer in chronic renal illness. However, the clinical data associated with CKD was not looked at the context of prostate cancer. The study aims to investigate prostate cancer risk in CKD patients using clinical data via systemic review and meta-analysis. Materials and Methods: Using pertinent pairing keywords, I carried out a thorough exploration of PubMed/MEDLINE and Web of Science. The pooled HR with 95% CI of the considered clinical findings was estimated involving the general inverse variance outcome type. With RevMan 5.3, the total pooled estimate meta-analysis was evaluated utilizing the random effects model. Results: Total of six findings were considered for this analysis, with a total of 2,430,246 participants. The age and mean follow-up of the included patients and studies ranged from 55 to 67.4 years and 10.1 to 12 years, respectively. The meta-analysis showed no significant risk of prostate cancer among CKD patients (HR: 0.92; 95% CI: 0.60-1.41; P = 0.70). The results from subgroup analysis based on eGFR levels ranged ≥30-59 ml/min per 1.73 m2 and also found no significant risk of prostate cancer among CKD patients (HR: 1.04; 95% CI: 0.92-1.18; P = 0.52). Here I did not report statistical heterogeneity found (Q = 0.56, I2 = 0%, P = 0.87). As per the Newcastle-Ottawa scale, the included studies suggested good quality. Conclusion: The results suggest no significant risk of developing prostate cancer among CKD patients. Therefore, well-designed prospective cohort studies with stages of CKD and clear predefined prior history and causative factors are needed to support the present evidence strongly.